Comparison of urban growth patterns and changes between three urban agglomerations in China and three metropolises in the USA from 1995 to 2015. (October 2019) - He, Qingsong; Zeng, Chen; Xie, Peng; Tan, Shukui; Wu, Jiayu
Highlights: The urban growth pattern and change in the three urban agglomerations in China and the USA were compared. Diffusional sprawl in the three Chinese Urban Agglomerations is more obvious than those in the USA. Urban sprawl process in China manifests itself as "engulfing" whereas it becomes "breeding" in the USA. Abstract: Urban sprawl is a worldwide significant challenge for a sustainable urban development. This study compared China, with its unprecedented urbanisation process, and the USA, with its long-standing campaign urban sprawl, as case study areas. The urban growth pattern was quantitatively identified in three noted urban agglomerations (the Yangtze River Delta, the Pearl River Delta, and the Beijing-Tianjin-Hebei urban agglomerations) in China and in three megalopolises (the Great Lakes Megalopolis, the Northeast Megalopolis, and the Californian Megaregion) in the USA at the patch level. The periods from 1995 to 2005 and from 2005 to 2015 were investigated, and the sprawl characteristic in infilling, edge, and outlying expansion patches were compared. The main findings include: 1) more than half of the outlying urban sprawl occurs within a distance of 4 km from the current primary construction centre in the USA. In China, the range of outlying urban sprawl is more extensive with a radius of 4–10 km; 2) the edge urban sprawl is the primary sprawl type in both countries; however, the proportion of edge-expansion land in China's metropolises is higher than in the USA, and edge expansion mainly occurs in the core cities of China's metropolitan areas; 3) with respect to infilling compact growth, more than a 20% increase of area and a more balanced pattern were observed in the three megalopolises in the USA during both periods, which is considerably higher than in China. The exploration on the differences and similarities between both countries provides an important reference toward optimised urban spatial planning in other countries.